Solidago canadensis L. Essential Oil Vapor Effectively Inhibits Botrytis cinerea Growth and Preserves Postharvest Quality of Strawberry as a Food Model System - Liu, Shumin; Shao, Xingfeng; Wei, Yanzhen; Li, Yonghua; Xu, Feng; Wang, Hongfei (Frontiers in Microbiology, 2016)
This study investigated the anti-fungal properties of Solidago canadensis L essential oil (SCLEO) against Botrytis cinerea in vitro, and its ability to control gray mold and maintain quality in strawberry fruits. SCLEO exhibited dose-dependent antifungal activity against B. cinerea and profoundly altered mycelial morphology, cellular ultrastructure, and membrane permeability as evaluated by scanning electron microscopy, transmission electron microscopy, and fluorescence microscopy. SCLEO vapor at 0.1 mL/L maintained higher sensory acceptance and reduced decay of fresh strawberry fruit, and also reduced gray mold in artificially inoculated fruit. SCLEO treatment did not however, stimulate phenylalanin ammonia-lyase (PAL), polyphenol oxidase (POD), or chitinase (CHI), enzymes related to disease resistance. This suggests that SCLEO reduces gray mold by direct inhibition of pathogen growth. SCLEO vapor may provide a new and effective strategy for controlling postharvest disease and maintaining quality in strawberries.